Venture Cycles: Theory and Evidence - Thomas Gehrig; Rune Stenbacka (Center for Economic Studies and ifo Institute (CESifo), 2003)
We demonstrate how endogenous information acquisition in venture capital markets creates investment cycles when competing financiers undertake their screening decisions in an uncoordinated way, thereby highlighting the role of intertemporal screening externalities induced by competition among venture capitalists as a structural source of instability. We show that uncoordinated screening behavior of competing financiers is an independent source of fluctuations inducing venture investment cycles. We also empirically document the existence of cyclical features in a number of industries such as biotechnology, electronics, financial services, healthcare, medical services and consumer products.
Keywords: 330; screening; venture capital; investment cycles